2015
DOI: 10.2337/db15-0384
|View full text |Cite
|
Sign up to set email alerts
|

ASK1 Inhibitor Halts Progression of Diabetic Nephropathy in Nos3-Deficient Mice

Abstract: p38 mitogen-activated protein kinase (MAPK) signaling promotes diabetic kidney injury. Apoptosis signal-regulating kinase (ASK)1 is one of the upstream kinases in the p38 MAPK-signaling pathway, which is activated by inflammation and oxidative stress, suggesting a possible role for ASK1 in diabetic nephropathy. In this study, we examined whether a selective ASK1 inhibitor can prevent the induction and progression of diabetic nephropathy in mice. Diabetes was induced in hypertensive endothelial nitric oxide syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 42 publications
(54 reference statements)
4
55
0
Order By: Relevance
“…Our study has identified a strategy for achieving similar levels of diabetes in male and female Nos3‐/‐ mice. As previously shown (Tesch et al ), male mice develop significant diabetes at week 1 after the fifth injection of STZ (55 mg/kg/day), which subsequently reaches a stable plateau at week 3. In comparison, female mice are more resistant to developing diabetes, but will achieve a similar level of diabetes as males from week 3 if they are given an extra (sixth) injection of STZ at 1 week after the fifth injection.…”
Section: Discussion/conclusionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study has identified a strategy for achieving similar levels of diabetes in male and female Nos3‐/‐ mice. As previously shown (Tesch et al ), male mice develop significant diabetes at week 1 after the fifth injection of STZ (55 mg/kg/day), which subsequently reaches a stable plateau at week 3. In comparison, female mice are more resistant to developing diabetes, but will achieve a similar level of diabetes as males from week 3 if they are given an extra (sixth) injection of STZ at 1 week after the fifth injection.…”
Section: Discussion/conclusionsupporting
confidence: 70%
“…Real‐time RT‐PCR was performed on a StepOne machine (Applied Biosystems, Mulgrave, VIC, Australia) with thermal cycling conditions of 50°C for 2 min, 95°C for 10 min, followed by 40 cycles of 95°C for 15 sec and 60°C for 1 min. Primers and FAM‐labeled MGB probes for detection of CD68, TNF‐ α , CCL2, KIM‐1, TGF‐ β 1, fibronectin, and collagen I and IV have been described previously (Tesch et al ). Primers and VIC‐labeled probes for 18S ribosomal RNA were purchased from Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%
“…ASK1 signals through a cascade of downstream kinases including p38 and c-Jun N-terminal kinase (JNK), leading to target gene expression including inflammatory cytokines 131132 . A preliminary report suggests that ASK1 inhibition substantially improves glomerulosclerosis in a diabetic animal model 133 . Gilead Sciences has initiated a 300 patient phase 2 program to test the efficacy of the selective ASK1 inhibitor GS-4997 in diabetic nephropathy.…”
Section: Anti-inflammatory Therapymentioning
confidence: 99%
“…Several issues need to be clarified, however. ASK1 inhibition did not improve podocyte loss and albuminuria in experimental diabetic CKD, suggesting that this kinase is not central for glomerular injury (73). Furthermore, the impact of ASK1 inhibitors in nondiabetic CKD is unknown.…”
Section: Targeting Redox Regulation In the Pathogenesis Of Nafld And Ckdmentioning
confidence: 99%